A scoping review of COVID-19 economic response policies in the MENA countries: lessons learned for Iran for future pandemics - Alireza Hajizadeh; Mohammad Seyedmohammadi; Shirin Nosratnejad; Behzad Najafi; Homayoun Sadeghi-bazargani; Ali Imani (Health Economics Review, 2024)
Abstract Background Given the significant impact of the COVID-19 pandemic, it is imperative to examine the economic response policies implemented by governments. This study aims to review evidence from the Middle East and North Africa (MENA) region, including Iran, on COVID-19 economic response policies designed to protect households, vulnerable groups, and businesses. Methods Utilizing Arksey and O’Malley’s scoping review methodology, electronic search engines and databases were systematically searched to identify published studies within the timeframe of December 31, 2019, to 2022. Additionally, a gray literature search for relevant policy documents and reports was conducted. The following six-step approach was employed: (1) defining the review questions, (2) identifying relevant studies through database searches, (3) screening studies for inclusion, (4) extracting and charting data, (5) analyzing and presenting results, and (6) providing guidance and suggestions. Narrative synthesis was utilized for data analysis. Results After a rigorous screening process, 53 studies were selected from a pool of 3392 search results. The findings are categorized into three primary groups: Households, vulnerable groups, and economic businesses. The majority of MENA countries implemented economic and social measures to support these groups, including stimulus packages, tax deferrals and exemptions, wage subsidies, and debt obligation deferments. The size of stimulus packages in MENA countries varied significantly, ranging from 0 to 14% of real Gross Domestic Product (GDP). The average stimulus package size in MENA countries was 3.67%, notably lower than the global average of 11%. Among the 64 selected countries, the average government support as a share of GDP was 6.3%, with Ecuador at the lowest (0.05%) and Germany at the highest (23%). In Iran, government financial support contributed approximately 7% to the Gross National Product. Conclusion MENA countries, including Iran, implemented diverse economic strategies and policies in response to the critical circumstances of the COVID-19 pandemic, tailored to their specific conditions. Assessing the effectiveness of these policies and the extent of the pandemic’s long-term economic, health, and lifestyle impacts requires a more extended timeframe.